Feedback System in Educational Games: A Systematic Literature Review - Aditya Sudyana; Atina Putri; Yusep Rosmansyah (Publikasi Indonesia, 2024)
The presence of a feedback system is a key factor in maintaining individuals' engagement in educational games. This system aims to enhance player motivation and active participation in educational games. In addition, the feedback system can improve the players' learning outcomes by augmenting their knowledge. Nevertheless, there remains a lack of comprehensive research in the field of feedback systems in educational games, leading to an inadequate comprehension of how to construct a proficient feedback system that can more effectively accomplish the objectives of educational games. The overview of feedback systems in educational games is frequently scattered and fragmented, making it challenging to figure out which educational games incorporate such systems. This research not only improves the comprehension of the feedback system in educational games but also addresses an important gap in the existing literature. The aim of this study is to conduct an extensive and systematic review of the existing literature on feedback systems in educational games. This review is based on 36 relevant journal articles published from 2019 to 2023. This research examines the patterns in the utilization of feedback systems in educational games, including the technologies employed to build these systems, the educational domains studied, and the types of products developed through the creation of educational games. In this study, the discussion also includes the design techniques and methods for feedback systems. This text discusses the utilization feedback types as well as the algorithms used to analyze the feedback systems. The text thoroughly discusses the comprehensive selection of feedback components to be delivered as mediums for player feedback. In this paper, we will clarify the impact of using feedback systems in educational games on the players. This study greatly contributes to the progress of learning conducted through educational games.